Children's Brain Development Benefits from Longer Gestation - Davis, Elysia P.; Buss, Claudia; Muftuler, Tugan; Head, Kevin; Hasso, Anton; Wing, Deborah; Hobel, Calvin; Sandman, Curt A. (Frontiers in Psychology, 2011)
Disruptions to brain development associated with shortened gestation place individuals at risk for the development of behavioral and psychological dysfunction throughout the lifespan. The purpose of the present study was to determine if the benefit for brain development conferred by increased gestational length exists on a continuum across the gestational age spectrum among healthy children with a stable neonatal course. Neurodevelopment was evaluated with structural magnetic resonance imaging (MRI) in 100 healthy right-handed six to ten year old children born between 28 and 41 gestational weeks with a stable neonatal course. Data indicate that a longer gestational period confers an advantage for neurodevelopment. Longer duration of gestation was associated with region-specific increases in grey matter density. Further, the benefit of longer gestation for brain development was present even when only full term infants were considered. These findings demonstrate that even modest decreases in the duration of gestation can exert profound and lasting effects on neurodevelopment for both term and preterm infants and may contribute to long-term risk for health and disease.